Parsley—Petroselinum crispum (Mill.) Nym. - James M. Stephens (EDIS)
This document provides an overview of parsley (Petroselinum crispum), detailing its historical origins, varieties, cultivation practices, and culinary uses. It highlights parsley's adaptability to Florida's climate, its nutritional benefits, and its popularity as both a garden and container-grown herb. The guide includes planting tips, care instructions, and harvesting methods, emphasizing its value as a flavorful and healthful addition to meals. Original publication date May 1994.